Integrating salpingoscopy and immunohistochemistry to improve tubal infertility diagnosis: a retrospective cohort study - Alenova, Adalyat; Korkan, Anuar; Kauysheva, Almagul; Magalov, Islam (Frontiers in Reproductive Health, 2025)
IntroductionTubal factor infertility is one of the most prevalent and diagnostically complex causes of female infertility. Standard imaging modalities, including hysterosalpingography and laparoscopy, frequently fail to detect subtle mucosal or molecular abnormalities. This study investigated whether combining salpingoscopy with immunohistochemical (IHC) profiling improves diagnostic precision and prognostic assessment in women with tubal-factor infertility.MethodsThis retrospective observational cohort study included 197 women who underwent laparoscopy between April 2020 and February 2025. Salpingoscopy was used to grade mucosal pathology severity, and ampullary biopsies were analyzed by IHC for CD138, Ki-67, and estrogen/progesterone receptors. A composite prognosis score incorporated clinical history, duration of conservative therapy, salpingoscopic findings, and IHC results. Spearman's rank correlation assessed associations between diagnostic parameters and pregnancy outcomes (natural or assisted).ResultsHigher salpingoscopic severity scores were significantly associated with reduced pregnancy likelihood (r = −0.457; p < 0.0001). Elevated IHC scores similarly correlated with decreased conception rates (r = −0.263; p = 0.0002). Tubal dilations and adhesions showed negative associations with reproductive outcomes (r = −0.232; p = 0.001). In contrast, the composite prognosis score demonstrated a strong positive correlation with treatment success (r = 0.578; p < 0.0001).DiscussionIntegrating salpingoscopic visualization with IHC profiling enhances detection of subtle mucosal and molecular abnormalities that are frequently missed by conventional diagnostic approaches. This combined modality offers superior prognostic accuracy and may guide personalized surgical and assisted reproductive treatment strategies. Ethical approval was obtained from the Ethics Committee of the Kazakhstan Medical University «KSPH» (IRB-64-2023).